Analisis Agihan iklim Klasifikasi Oldeman Menggunakan Sistem Informasi Geografis di Kabupaten Cilacap - Kamala, Rifqi; , Drs. Yuli Priyana, M.Si; , Agus Anggoro Sigit, S.Si., M.Sc (2015)
Oldeman climate classification used for agriculture that determination based on the amount of water needs (rainfall) on food crops (rice plant and crops plant). Climate information by using the Geographic Information System (GIS) in its presentation further simplify the use and readability. Cilacap District is the largest district in Central Java province with agriculture as the largest contributor in the formation of Gross Domestic Product (GDP). Oldeman climate classification establish agroclimate zone that can determine how many times the planting period in a year. Therefore this research entitle ANALYSIS OF OLDEMAN CLIMATE CLASSIFICATION DISTRIBUTION USING GEOGRAPHICAL INFORMATION SYSTEM IN CILACAP DISTRICT. The purpose of this research is: (1) determine the distribution of the climate and agroclimate zone Oldeman classification in Cilacap, (2) determine the suitability of irrigation and agroclimate zone Oldeman classification in Cilacap Regency. The method used secondary data analysis and survey research areas. Analysis of secondary data such as rainfall data calculations based climate Oldeman classification, interpolation, and overlay. While survey research area emphasizes the use of the type of irrigation and growing season in the area. The results showed that the Cilacap District has seven climate type and agroclimate zone Oldeman climate classifications types are: A1, B1, B2, B3, C2, C3, and D3. Distribution of A1 type is Jeruklegi Subdistrict, North Cilacap Subdistrict, west side of Kesugihan Subdistrict, distribution of B1 type is center side of Kesugihan Subdistrict, Binangun Subdistrict, Nusawungu Subdistrict, distribution of B2 type is south side of Sampang Subdistrict, north side of Kroya Subdistrict, Maos Subdistrict, distribution of B3 type is north side of Sampang Subdistrict, north side of Maos Subdistrict, central side of South Cilacap Subdistrict, distribution of C2 type is west side of South Cilacap Subdistrict, west side of Kampung Laut Subdistrict, west side of Kawunganten Subdistrict, distribution of C3 type is west side of Patimuan Subdistrict, north side of Wanareja Subdistrict, east side of Dayeuhluhur Subdistrict, north side of Majenang Subdistrict, and distribution of D3 type is west side Dayeuhluhur Subdistrict. The type of irrigation used, there are five of them: technical irrigation, rainfed, irrigation simple, semi-technical irrigation, and rural irrigation. Areas that have appropiate between the types of irrigation and agroclimate zone are is South Cilacap Subdistrict, North Cilacap Subdistrict, Central Cilacap Subdistrict, Jeruklegi Subdistrict, east side of Kesugihan Subdistrict, north side of small Adipala Subdistrict, east and west side of Kawunganten Subdistrict, south side of Bantarsari Subdistrict, south side of Gandrungmangu and Kedungreja Subdistrict, Patimuan Subdistrict, Karangpucung Subdistrict, north side of Wanareja and Majenang Subdistrict, and Dayeuhluhur Subdistrict.